2021
DOI: 10.1111/1462-2920.15501
|View full text |Cite
|
Sign up to set email alerts
|

Indicator species drive the key ecological functions of microbiota in a river impacted by acid mine drainage generated by rare earth elements mining in South China

Abstract: Summary Acid mine drainage (AMD) generated by rare earth elements (REEs) deposits exploration contains high concentrations of REEs, ammonium and sulfates, which is quite different from typical metallic AMD. Currently, microbial responses and ecological functions in REEs‐AMD impacted rivers are unknown. Here, 16S rRNA analysis and genome‐resolved metagenomics were performed on microbial community collected from a REEs‐AMD contaminated river. The results showed that REEs‐AMD significantly changed river microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 96 publications
(133 reference statements)
1
13
0
Order By: Relevance
“…One of these genomes was assembled into a single scaffold using mate-pair reads. In addition, we identified 14 previously existing MAGs in GenBank derived from previous environmental metagenome projects [60][61][62][63][64][65][66][67][68][69][70][71]. Of these, five can be considered high quality (>90 % complete, <10 % contamination).…”
Section: Discussionmentioning
confidence: 99%
“…One of these genomes was assembled into a single scaffold using mate-pair reads. In addition, we identified 14 previously existing MAGs in GenBank derived from previous environmental metagenome projects [60][61][62][63][64][65][66][67][68][69][70][71]. Of these, five can be considered high quality (>90 % complete, <10 % contamination).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that different clades were found dominant in each analysis ( Figure 3 D), and only one sequence was identified in both analyses—WP_019899159.1 ( Table 1 ). Interestingly, we detected a relatively large number of sequences of XoxF1 (in particular, based on metaproteomic analyses), whereas studies of marine and terrestrial environments indicated that XoxF4 and XoxF5 are dominant [ 33 , 46 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our study extends the existing knowledge, as the metaproteomic analysis indicated the presence of XoxF even in the order of non-methanotrophic Xanthomonadales , precisely within the aerobic heterotroph Dokdonella koreensis DS-123, described by Yoon et al (2006) [ 45 ]. Only Chen et al (2021) [ 46 ] reported that, apart from Proteobacteria , XoxF is encoded by the genome of the FCB ( Fibrobacteres , Chlorobi , and Bacteroidetes ) group, which is a superphylum.…”
Section: Discussionmentioning
confidence: 99%
“…One of these genomes was assembled into a single scaffold using mate pair reads. In addition, we identified 14 previously existing MAGs in GenBank derived from previous environmental metagenome projects [52][53][54][55][56][57][58][59][60][61][62][63]. Of these, 5 can be considered high quality (>90% complete, <10% contamination).…”
Section: Discussionmentioning
confidence: 99%